2013
DOI: 10.1152/ajprenal.00353.2013
|View full text |Cite
|
Sign up to set email alerts
|

Hydration status affects sodium, potassium, and chloride transport across rat urothelia

Abstract: Recent data suggest possible net transport of urinary constituents across mammalian urinary tract epithelia (urothelia). To evaluate the effect of animal hydration status on such transport, we instilled urine collected during 2-day water deprivation, water loading, or ad libitum water intake into isolated in situ bladder(s) of groups of rats undergoing one of the same three hydration states. After 1-h bladder dwell, we retrieved the urine and measured differences in volume and solute concentrations between ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Na + transport across ex vivo rabbit urothelial tissue and water permeability of human bladder were demonstrated several decades ago. Investigation of the permeability of intact rabbit bladder urothelium by Negrete et al showed that this was low under normal conditions, consistent with the urothelium acting as an effective barrier. In vivo studies of animals under conditions of water deprivation or water loading have also been employed to investigate the permeability of the bladder to water and several ions.…”
Section: Measurement Of Urine Electrolyte Concentrations In Animals Amentioning
confidence: 88%
See 1 more Smart Citation
“…Na + transport across ex vivo rabbit urothelial tissue and water permeability of human bladder were demonstrated several decades ago. Investigation of the permeability of intact rabbit bladder urothelium by Negrete et al showed that this was low under normal conditions, consistent with the urothelium acting as an effective barrier. In vivo studies of animals under conditions of water deprivation or water loading have also been employed to investigate the permeability of the bladder to water and several ions.…”
Section: Measurement Of Urine Electrolyte Concentrations In Animals Amentioning
confidence: 88%
“…An interesting study of rats during water deprivation, water loading, or ad libitum H 2 O involved urine collection and its subsequent instillation into isolated in situ bladders from animals in the corresponding condition. Measurements of Na + , K + , and Cl − indicated that (1) the instilled urinary ion concentrations and (2) animal hydration status influenced the degree of water reabsorption across the urothelium leading the authors to conclude that urine composition was modified in the lower urinary tract …”
Section: Measurement Of Urine Electrolyte Concentrations In Animals Amentioning
confidence: 99%
“…Therefore, it was hypothesized that some channels in the urothelium function in the condition of full‐filled (distended) bladder because AQPs transport water only. Urea, sodium, and chlorine move across rat urothelial cells, but the underlying mechanism has not been elucidated. The epithelial sodium channel (ENaC) mediates sodium transport across the apical membrane of the urinary bladder epithelium .…”
Section: Discussionmentioning
confidence: 99%
“…; Spector et al. , , , ). Thus, at least small quantities of vectorial solute and water transport across urinary tract urothelia may be a feature of most or all mammalian species and the hibernating bear may or may not have unique urothelial transport capabilities enabling the net transport of urinary constituents.…”
Section: Introductionmentioning
confidence: 97%